Story-tellers: The image of the two-year college in American fiction and in women's journals - Nancy LaPaglia (Adult Education Research Conference, 1993)
American fiction portrays the two-year college student as a re-entry woman who is a passive loser. Journals written by re-entry women and women faculty reveal a different image.